2021
DOI: 10.1186/s12879-021-06019-5
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and genotype distribution of HPV infection among 214,715 women from Southern China, 2012–2018: baseline measures prior to mass HPV vaccination

Abstract: Background The epidemiology on the human papillomavirus (HPV) among females in Southern China is not well-established. Baseline data on the prevalence of HPV infection in China prior to mass prophylactic HPV vaccination would be useful. Thus, this study aims to determine the type-specific HPV prevalence and distribution among females from Southern China prior to mass HPV vaccination. Methods A retrospective cross-sectional study employing 214,715 w… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
35
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(45 citation statements)
references
References 28 publications
9
35
1
Order By: Relevance
“…The prevalence of HPV in northern Henan Province was lower than that reported in Shandong Province (28.4%) and Fujian Province (38.3%) [ 19 , 20 ], but higher than Yunnan Province (12.9%) and Shanxi Province (8.92%) [ 12 , 21 ]. The different HPV prevalence in northern Henan Province was expected and could have been due to the different economic conditions, living habits and customs, cultural diversity, sampling strategy, and the HPV detection methods [ 13 , 22 ]. According to the previous reports, the HPV infection rate ranges from 6.7 to 44.5% in China [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of HPV in northern Henan Province was lower than that reported in Shandong Province (28.4%) and Fujian Province (38.3%) [ 19 , 20 ], but higher than Yunnan Province (12.9%) and Shanxi Province (8.92%) [ 12 , 21 ]. The different HPV prevalence in northern Henan Province was expected and could have been due to the different economic conditions, living habits and customs, cultural diversity, sampling strategy, and the HPV detection methods [ 13 , 22 ]. According to the previous reports, the HPV infection rate ranges from 6.7 to 44.5% in China [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…The rate then generally declined from 18.35% in 2019 to 12.26% in 2021. Luo et al [ 14 ] showed that the HPV infection rate in southern China was trending down from 2012 to 2018, and that Xinjiang HPV infections peaked in 2014 [ 9 ]. It is worth noting that reported infection rates, and thus trends, may be affected by demographic factors (e.g., ethnicity and cultural diversity) and by technical factors, such as sampling strategies, equipment, methods, and the specificity and sensitivity of HPV detection analysis [ 9 , 13 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of HPV varied greatly in different provinces of China. There have been some studies reported the prevalence and genotype distribution of HPV in different provinces in China [10,11,12,13]. However, there are few reports on HPV prevalence in Henan Province.…”
Section: Discussionmentioning
confidence: 99%
“…HPV DNA ampli cation and genotyping were conducted using a commercial HPV genotyping kit for 37 HPV types, including 17 HR-HPV types (16,18,26,31,33,35,39,45,51,52,53,56,58,59,66,68,82) and 20 LR-HPV types (6,11,34,40,42,43,44,54,55,57,61,67,69,70,71,72,73,81,83,84). The kits have been authorized by the China Food and Drug Administration for clinical use.…”
Section: Dna Extraction Pcr Ampli Cation and Hpv Genotypingmentioning
confidence: 99%